Satellite navigation observation equations and theirs solution algorithm - Xigang Sun; Yuanfa Ji (2009 IEEE International Conference on Automation and Logistics, 2009)
The GPS positioning accuracy sometimes is poor for the big GDOP because of satellite distribution and the impact of systematic errors. To solve this problem, two sets of measurement equations were put forward in this paper: measurement equations subject to height constraint; hyperboloid measurement equations subject to height constraint, and Kalman filtering method was designed for solving these two different equations. Finally, these two methods were proved fast convergence and high precision through simulation tests comparing with general pseudo-range measurement equations.